2006
DOI: 10.1103/physrevlett.97.075501
|View full text |Cite
|
Sign up to set email alerts
|

Kink Formation and Motion in Carbon Nanotubes at High Temperatures

Abstract: We report that kink motion is a universal plastic deformation mode in all carbon nanotubes when being tensile loaded at high temperatures. The kink motion, observed inside a high-resolution transmission electron microscope, is reminiscent of dislocation motion in crystalline materials: namely, it dissociates and multiplies. The kinks are nucleated from vacancy creation and aggregation, and propagate in either a longitudinal or a spiral path along the nanotube walls. The kink motion is related to dislocation gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
82
0
7

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 22 publications
10
82
0
7
Order By: Relevance
“…[13][14][15][16] We found recently that a carbon nanotube can be Joule heated to temperatures higher than 2000°C by passing a high current through it. [17][18][19][20][21] It was also discovered previously that carbon onions 22,23 and carbon nanotubes can be used as high-pressure cells to generate high pressures. 13,[24][25][26] The question then arises: can we generate high pressures and high temperatures simultaneously by using carbon nanotubes as heaters and carbon onions as pressure cells?…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15][16] We found recently that a carbon nanotube can be Joule heated to temperatures higher than 2000°C by passing a high current through it. [17][18][19][20][21] It was also discovered previously that carbon onions 22,23 and carbon nanotubes can be used as high-pressure cells to generate high pressures. 13,[24][25][26] The question then arises: can we generate high pressures and high temperatures simultaneously by using carbon nanotubes as heaters and carbon onions as pressure cells?…”
mentioning
confidence: 99%
“…A twoterminal connection was made to individual nanotubes by using a Nanofactory transmission electron microscopyscanning tunneling microscopy (TEM-STM) platform. [17][18][19][20][21] Once a connection was made, we then ran a high current through the nanotubes to heat the nanotubes and onions to high temperatures. From the melting and evaporation of highmelting-point ceramics, the graphitization of the nanotube walls, and the blackbody radiation spectroscopy, 27 it was proved that a temperature of ∼2000°C was reached in the nanotubes and carbon onions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, it can have a positive effect, especially when combining the significant random agitation of the atoms with a coherent component caused by an externally applied deformation. For example, recent experiments on superplasticity 3,4 obtained that CNTs under tensile load can undergo large elongation and thinning without abandoning their perfection. Theoretical studies [5][6][7] indicated that superplasticity relies on primary microscopic mechanisms, like a mass-conserving glide along a helical slip path, as well as on a nearly axial kink propagation with dimers directly breaking out of the lattice.…”
mentioning
confidence: 99%
“…Screw vectors have components along translational and circumferential vectors. The three Burgers vectors of graphene 4 indicate three nonequivalent helical slip paths for CNTs. We will show with direct objective MD calculations that the path indicated by the screw Burgers vector b with the smallest component in the circumferential direction is desirable under twist.…”
mentioning
confidence: 99%